Analisis Usability Alur Pencarian Pada Aplikasi Belanja Online Berbasis Android Dengan Model GOMS - Andika Sujar Adi Saputra; Hanifah Muslimah Az-Zahra; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Online shopping application or also known as e-commerce is a device for spreading, selling, purchasing, marketing goods and services through electronic system such as internet. Among so many e-commerce industries in Indonesia, two of them are Lazada and Matahari Mall. They are online shopping sites that offer several advantages in daily needs. In the early observation, the researcher found the satisfaction aspect, experience and effectiveness in using the application, those aspects are important point in developing the products. Method or scientific model which can help in finding out user's needs to design the product that can fulfill the user's needs, is doing analysis on the users themselves. Analysis on users can be done by GOMS (Goals, Operator, Method, and Selection) model, which is task analysis model. Beside using GOMS, to measure efficiency and the use of the application needs usability method. Usability is one of the user experience. To measure the usability level from an application, we need an approach using USE (Usefulness, Satisfaction, and Ease of use) questionnaire at 1-7 likert scale. Usability level measurement is done to know the level of the usability from Lazada and Matahari Mall and also to know the score of usability level on recommendation design which is a new prototype and result from this research.